(untitled) (Global Journal of Medical Research, 2024)
Dental amalgam contains 50 mercury copper silver and tin These metals bathed in acid saliva form a battery Experience collaborating with a mercury-free dentist indicates that the metallic dental fillings most urgently needing replacement are those with the highest associated voltages 100mVs Electrical curre nts caused by mercury amalgam dental fillings are liable to be associated with chronic illness and replacing them with non-metallic non-toxic dental material can be therapeutic An ea rthing mat 9 that removes static electricity from patients with high-voltage mercury amalgam dental fillings can cause symptomatic relief Two clinical cases are presented as evidence of the concept